1989
DOI: 10.1093/ajcn/50.3.689
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary findings on iron supplementation and learning achievement of rural Indonesian children

Abstract: The effects of oral iron supplementation on blood iron levels and learning achievement in 130 rural Indonesian school children were assessed in this double-blind study. The children were classified into anemic and nonanemic groups according to their initial hemoglobin and transferrin saturation levels and were randomly assigned to either iron or placebo treatment for 3 mo. Hematological, anthropometric, and learning-achievement data were collected before (T1) and after (T2) the treatment period and 3 mo later.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
90
0
1

Year Published

1998
1998
2023
2023

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(107 citation statements)
references
References 7 publications
1
90
0
1
Order By: Relevance
“…Kashyap et al 34 Soemantri et al 56 Ayoya et al 17 Sungthong et al 57 Pollitt et al 44 Mean Overall school grades Gopaldas et al [29][30][31] Pollitt et al 44 Seshadri et al 28 Kashyap et al 34 Seshadri et al 17 Gopaldas et al [29][30][31] Pollitt et al 44 Seshadri et al 28,55 (study 2)…”
Section: Studymentioning
confidence: 99%
“…Kashyap et al 34 Soemantri et al 56 Ayoya et al 17 Sungthong et al 57 Pollitt et al 44 Mean Overall school grades Gopaldas et al [29][30][31] Pollitt et al 44 Seshadri et al 28 Kashyap et al 34 Seshadri et al 17 Gopaldas et al [29][30][31] Pollitt et al 44 Seshadri et al 28,55 (study 2)…”
Section: Studymentioning
confidence: 99%
“…Previous research has shown the detrimental effect of iron deficiency on adult labor force productivity [Thomas et al, 2006] 6 , but to date there is no rigorous evidence that IDA is an important contributing factor 4 See, for instance: Seshadri et al [1982]; ; ; Groner et al [1986]; Kashyap and Gopaldas [1987]; Seshadri and Gopaldas [1989]; Soemantri [1989]; Bruner et al [1996]. One large study in Thailand could not replicate the beneficial effects of iron supplementation found in other settings (Pollitt et al, 1989;Sungthong et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…In Indonesia (Soemantri et al, 1985;Soemantri, 1989), Thailand (Pollitt et al, 1989), and India (Seshadri & Gopaldas, 1989) indications are that iron de®ciency anemia in adolescence is associated with poor performance on academic tests and that iron supplementation signi®cantly improves test results. It has also been found that adolescents treated with iron supplements show improvement in their ability to concentrate (Balin et al, 1992).…”
Section: Introductionmentioning
confidence: 99%